Importance of supplementation with coenzyme Q10 in combating free radicals obtained in high intensity physical activity: a literature review (Research, Society and Development, 2021)
Introduction: Physical activity in due moderation brings benefits to our health. However, when in excess, it causes physical wear and tear, causing several damages to health such as muscle damage, formation of free radicals, oxidative stress and degenerative diseases. Coenzyme Q10 (CoQ10) is an essential benzoquinone for life, and is present in all cells of the human body, being known for its antioxidant role, the present study aimed to identify the relationship of CoQ10 supplementation after intense physical activity of different sports modalities. Methodology: A literature review study was carried out in Portuguese, English and Spanish in the electronic databases CAPES, Pubmed, Scientific Electronic Library Online (SCIELO) and Scholar Google (Google Academic). Those who met the inclusion criteria were selected, as inclusion criteria, the articles should address issues related to the aforementioned descriptors. Result: Physical exercises that exceed the physiological limit, overtraining, tend to promote an increase in the production of free radicals known as Reactive Oxygen Species (ROS) in the body, which when not neutralized can initiate a deleterious process in cells and tissues, causing various degenerative diseases. CoQ10 is a substance produced by our body and can also be acquired from exogenous sources. It has a powerful antioxidant action and represents a key component of the mitochondrial respiratory chain generating energy. Conclusion: According to the studies studied, it was observed that CoQ10 has a powerful antioxidant action in fighting free radicals, which are formed in intense physical activity practitioners.